Voluntary Counselling and Testing (VCT) HIV and Sexually Transmitted Diseases (STD) Detection among People Living in the Bontomangape Health Center Service Area, Galesong, Takalar: Pos Voluntary Councelling and Testing (VCT) HIV dan Deteksi Infeksi Menular Seksual (IMS) pada masyarakat di Wilayah Kerja Puskesmas Bontomangape, Galesong, Takalar - Yusuf, Yenni; Amiruddin, Dianawaty; Mubin, Risna Halim (Yayasan Ahmar Cendekia Indonesia, 2024)
The incidence of HIV in the Bontomangape Galesong Health Center work area has raised a concern for Hasanuddin University (UNHAS). Partnering with the health center, UNHAS team carried out Voluntary Counseling and Testing (VCT) posts to educate the community and to conduct early detection of HIV in the health center work area. The activities in the VCT post included the playing of educational videos, the distribution of HIV andsexually transmitted diseases (STD) educational leaflets, counseling to undertake tests for family members of people with HIV, counseling to do tests on the people at risk, rapid antigen HIV-Syphilis examination, and post-screening counseling. The results and outputs produced in program were (1) HIV and STD educational videos and leaflets, (2) Publication in the online media, and (3) Increased public knowledge and awareness regarding the dangers and risk factors of HIV, and the importance of early detection of HIV and STI. Abstrak Tingkat kejadian HIV di daerah pesisir termasuk di wilayah kerja Puskesmas Bontomangape Galesong menjadi perhatian Universitas Hasanuddin (UNHAS). Bermitra dengan pihak puskesmas, tim UNHAS melaksanakan pos Voluntary Counselling and Testing (VCT) untuk edukasi dan skrining HIV di wilayah kerja puskesmas. Kegiatan pos VCT termasuk pemutaran video edukasi dan penyebaran leaflet HIV dan Infeksi menular seksual (IMS), konseling untuk melakukan tes bagi para anggota keluarga ODHIV, konseling test pada masyarakat umum yang beresiko, pemeriksaan rapid antigen HIV-Sifilis, dan konseling pasca skrining. Luaran yang dihasilkan pada kegiatan ini adalah (1) Video dan leaflet edukasi HIV dan IMS, (2) Publikasi pada media online, dan (3) meningkatnya pengetahuan dan kesadaran masyarakat mengenai bahaya dan faktor risiko HIV, serta pentingnya deteksi dini HIV dan IMS.